Peripheral urbanization: autoconstruction, transversal logics, and politics in cities of the global south - Caldeira, Teresa Pires do Rio (ANPUR, 2024)
Many cities around the world have been largely constructed by their residents, who build not only their own houses, but also frequently their neighborhoods. In this article, I use the notion of peripheral urbanization to analyze this way of producing cities that is quite pervasive in the global south. I argue that peripheral urbanization refers to modes of the production of space that (a) operate with a specific temporality and agency, (b) engage transversally with official logics, (c) generate new modes of politics, and (d) create highly unequal and heterogeneous cities. I also argue that peripheral urbanization not only produces heterogeneity within the city as it unfolds over time, but also varies considerably from one city to another. I build my arguments by juxtaposing dissimilar cases from a few cities in the global south. To focus on peripheral urbanization means simultaneously to de-center urban theory and to offer a bold characterization of modes of the production of space that are different from those that generated the cities of the North Atlantic. Diversas cidades ao redor do mundo foram criadas em grande parte por seus moradores, que constroem não apenas suas próprias casas, como também, frequentemente, seus bairros. Neste artigo, utilizo a noção de urbanização periférica para analisar essa forma de produzir cidades, bastante difundida no sul global. Argumento que a urbanização periférica se refere a modos de produção do espaço que (a) operam com uma temporalidade e agência específicas, (b) interagem transversalmente com lógicas oficiais, (c) geram novas práticas políticas e (d) criam cidades profundamente desiguais e heterogêneas. Argumento, ainda, que a urbanização periférica não só produz heterogeneidade dentro da cidade, à medida que se desenvolve ao longo do tempo, como também varia consideravelmente de uma cidade para outra. Construo meus argumentos por meio da justaposição de casos dissimilares de cidades do sul global. Analisar a urbanização periférica significa tanto descentralizar a ...